Sero-Epidemiological Investigationof Hepatitis A Virus (HAV) and Hepatitis E Virus (HEV) among Acute Viral Hepatitis Cases at a Tertiary Care Centrein Punjab - Ruchika, Dr; Dr. Rupinder Bakshi; Dr. Satinder Kaur; Dr. Satinder Kaur; Dr. Palika Sharma; Dr. KarashdeepKaur (GMC Patiala Journal of Research and Medical Education, 2024)
Abstract:BACKGROUND:Acute viral hepatitis, primarily caused by enteric viruses like hepatitis A (HAV) and hepatitis E (HEV) carry a significant health burden in India. It poses serious health concerns due to their link with inadequate hygiene and sanitation practices.AIM:In a tertiary care facility in Punjab, North India, the current study sought to determine the prevalence of the hepatitis A and hepatitis E viruses in patients who were presenting with acute viral hepatitis.MATERIAL AND METHOD:A total of 483 serum samples collected from tertiary care hospital in 2022 were analyzed for IgM antibodies against HAV and HEVusing rapid diagnostic tests(RDTs).RESULTS:The results revealed a higher incidence of HAV IgM positivity (13.4%) compared to HEV IgM positivity (8.7%). The combined prevalence of HAV and HEV infections was 22.15%. Gender-wise analysis showed a higher incidence of Hepatitis A in males, while Hepatitis E was more prevalent among females. Additionally, the study found a higher incidence of enteric viral hepatitis in males compared to females. Age-wise distribution indicated a higher proportion of HAV-positive cases in patients < 20 years (76.9%) and HEV-positive cases in young adults of age group 21-30 years (50%). Seasonal variation demonstrated the prevalence of both viruses throughout the year, with peaks in cases observed at the end of the monsoon season and the beginning of winter in this geographical region.CONCLUSION:The study highlights a higher prevalence of Hepatitis A Virus (HAV) as compared to Hepatitis E Virus (HEV) among suspected Acute Viral Hepatitis cases, emphasizing a significant public health concern, and underscores the need for targeted interventions and sanitation measures in our region.